In Silico Study of Monascus sp. Pigment Derivatives as Anticardiovascular Candidate - Dichy Nuryadin Zain; Anna Yuliana (Universitas Islam Indonesia, 2023)
Abstract Background: Cardiovascular disease is the leading cause of death in the world. The therapeutic activity of Monascus sp. pigment can act as an anticardiovascular agent. Research on Monascus sp. pigment is rapidly developing, including the discovery of new pigments, the methods used, and their identification. Currently, there are 57 dyestuff compounds that have been successfully isolated from Monascus molds. So, researchers conducted an in-silico study of Monascus sp.Objective: To determine whether it can have better interactions and activities as an anticardiovascular medicine candidate.Method: PAK1 is used as a receptor for anticardiovascular drugs. 57 test compounds were carried out for ligand preparation and application of Lipinski's rule of five by using MarvinSketch software, ADME prediction and toxicity testing using PreADMET, the docking process using Autodock tools, and visualization using Discovery Studio.Results: The results of the docking analysis are seen from the values of binding affinity consecutively. compound R3 (-8.74 kcal/mol), red shandong (-8.16 kcal/mol), and monaphilol (-8.14 kcal/mol) are lower than the comparison compound bisoprolol (-6.44 kcal/mol), which shows that the three compounds have better interactions than the comparison compounds. Conclusion: Derivative compounds from Monascus sp. Pigment are predicted to have better interactions and can be used as anticardiovascular medicine candidates.Keywords: Monascus sp., pigment, anticardiovascular, in silico, PAK1, ADME, and toxicity